2021
DOI: 10.1371/journal.pone.0260819
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with anxiety and depression amongst hospitalised COVID-19 patients in Laquintinie Hospital Douala, Cameroon

Abstract: Studies assessing the mental health of patients with COVID-19 infection remain limited. Disasters and major emergencies, not just COVID-19, undoubtedly lead to greater incidence of mental health problems. Previous studies indicate that the novel Coronavirus disease can cause panic and stress in patients. Our literature search didn’t reveal any previous published data from Cameroon and the Central African sub-region. In order to bridge this gap, we assessed the prevalence and factors associated with depression … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 24 publications
5
15
0
Order By: Relevance
“…This finding is in line with the previous study conducted in Cameroon [46]. The observed association of high levels of anxiety with COVID-19 complications has been demonstrated in a study by Mazza et al [47].…”
Section: Plos Global Public Healthsupporting
confidence: 92%
“…This finding is in line with the previous study conducted in Cameroon [46]. The observed association of high levels of anxiety with COVID-19 complications has been demonstrated in a study by Mazza et al [47].…”
Section: Plos Global Public Healthsupporting
confidence: 92%
“…Their own anxiety and depression were independent risk factors for depression and anxiety, respectively. Similar to our findings, anxiety was an independent risk factor for depression, and depression was a risk factor for anxiety in COVID-19 patients [ 25 ]. Collectively, these studies indicated that it could present interactions between anxiety and depression in infertile couples.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is likely related to beliefs of Cameroonian about deleterious effects of vaccines including COVID-19 vaccines. This has likely played a great role in increasing rates of psychological disorders such as depression and anxiety among African populations [17,18]. High rates of COVID-19 vaccine hesitancy was also found in South East Asia [19].…”
Section: Discussionmentioning
confidence: 99%